The Arab lands under Ottoman rule - Hathaway, Jane, 1962- author.
1 online resource.
Keywords: "The Arab Lands under Ottoman Rule assesses the effects of Ottoman rule on the Arab Lands of Egypt, Greater Syria, Iraq and Yemen between 1516 and 1800."--